In-plane growth of germanium nanowires on nanostructured Si(001)/SiO2 substrates. Issue 3 (20th August 2020) - Lange, Felix; Ernst, Owen; Teubner, Thomas; Richter, Carsten; Schmidbauer, Martin; Skibitzki, Oliver; Schroeder, Thomas; Schmidt, Peer; Boeck, Torsten
Abstract: Germanium (Ge) nanowires (NWs) were grown in-plane on nano-structured Si(001)/SiO2 substrates by molecular beam epitaxy using gold (Au) as the solvent. The site-selective NW growth was enabled by a rectangular array of gold droplets on silicon (Si) tips with an Au nuclei density below 0.25 µ m −2 on the surrounding silicon oxide (SiO2 ). The initial growth of Ge NWs starting from Si–Au droplets with Six Ge1−x nucleation from ternary alloy is discussed from a thermodynamic point of view. The in-plane NW elongation occurred within ⟨110⟩ directions on the substrate and NWs were mainly bounded by two 55° inclined 111 facets and a less pronounced planar (001) top facet. Fully relaxed crystal lattices of Ge NWs were observed from two-dimensional reciprocal space maps of x-ray diffraction measurements.